Dual and Axenic culture of Sclerospora graminicola on Pearl Millet and in vitro raised disease resistant host germplasm - D.V. Rao and Savita Sagwan (Journal of Applied Pharmaceutical Science, 2013)
Mother axis of the infected suppressed ear-head of pearl-millet with embryoids was sliced (2-3 mm) and surface sterilized with 0.2 % Ethyl mercuric chloride followed by repeated washings with sterile antioxidant solution (50 mg/L citric acid, 25 mg/L ascorbic acid and 50 mg/L P.V.P). Sterilized slices were cultured on modified MS medium supplemented with 10 mg/L IAA, 0.5 mg/L Kinetin, 2.5 mg/L 2,4-D, 3.0 mg/L casein hydrolysate, 25 mg /L ascorbic acid and 150 mg/L coconut water. Two types of calli were formed after 10-15 days. Slow growing compact milky coloured was embryogenic and the other hyaline fast-growing was non-embryogenic. The fungus grew on the callus after 20-25 days of inoculation. It grew axenically on the surface of the medium after sometime. Slow growing embryogenic callus was subcultured to auxin free ¾ strength MS medium with 25 mg/L ascorbic acid, 100 ml/L coconut water and 0.5 mg/L Kinetin. Regeneration plantlets were transferred for rooting on ½ strength MS medium containing 1.5 mg/L IBA and 25 mg/L ascorbic acid. The regenerated plantlets with strong root system were transferred to 4 earthen pots. The plantlets raised were subjected for disease resistance by growing them on the medium containing different concentrations of the fungus filtrate. The plantlets showing resistance have been accepted as diseases resistant.
Keywords: Suppressed ear-head diseases, Embryogenic, Axenicall